Der Beginn des Untergangs : die Zerstörung der jüdischen Gemeinden in Polen und das Vermächtnis des Wilnaer Komitees - Schulz, Miriam (Reihe ZeitgeschichteN, 2016)
Two months after the outbreak of the Second World War, sixty Jewish writers and journalists in Vilnius formed a committee to document the destruction of Polish Jewry. This was probably the earliest Jewish historical commission in Eastern Europe, working in the shadow of German crimes. This study explores the six bulletins issued by the committee, translated from the Yiddish to German